Higher‐dimensional Reidemeister torsion invariants for cusped hyperbolic 3‐manifolds. (4th July 2013) - Menal-Ferrer, Pere; Porti, Joan
Abstract : For an oriented finite volume hyperbolic 3‐manifold M with a fixed spin structure η, we consider a sequence of invariants T n ( M ; η)